(untitled) (International Journal of Communication Systems and Network Technologies, 2019)
Every educational institute brings enormous opportunities for students to learn and showcase their talent in the form of a number of workshops. These workshops are organized by a number of clubs, societies, technical sub organizations and sub organizations. Each organization has a faculty coordinator, student head and a number of volunteers working under it. The counting is huge when it comes to the number of clubs a college can have and a number of events a club can organize, to there is need for a common portal where student can look for all the events happening in their college under several clubs and be able to enrol for their interested event without much effort at a common place. Clubs portal is one step platform fulfilling the above requirement.